ENHANCING THE PHOTOLUMINESCENCE OF POLYFLUORENE-BASED THIN FILMS VIA ILLUMINATION - PETROVAI, Ioan; TODOR-BOER, Otto; DAVID, Leontin; BOTIZ, Ioan (Studia Universitatis Babeș-Bolyai Physica, 2022)
We show in this work that exposing thin films of conjugated poly[9,9-bis(2-ethylhexyl)-9H-fluorene-2,7-diyl] to light under nitrogen atmosphere led to an increase of their emission up to 2.2 folds. This enhancement was due to the appearance of structural changes in the glassy and β-phase conformations induced upon thin film illumination, as revealed by the Franck-Condon analysis of the photoluminescence spectra. Interestingly, the photoluminescence of thin films remained at the enhanced value for 75 days after stopping the illumination, most probably due to the permanent structural changes induced upon illumination.